Taxonomic study of the genus Tabanus Linnaeus, 1758 (Diptera: Tabanidae) in East Azarbaijan province with three species as new records for the Iranian fauna - Fatemeh Moayyed Mazraeh; Samad Khaghaninia; Shahzad Iranipour; Ali Yavuz Kilic (Journal of Insect Biodiversity and Systematics, 2018)
Based on specimens collected from East Azarbaijan province during 2016–2017 as well as specimens which already had been collected during 2007–2015 and deposited at ICHMM, overall 18 species of the genus Tabanus were recognized which among them, Tabanus armenicus (Krober, 1928), Tabanus maculicornis Zettersted, 1842 and Tabanus nemoralis Meigen, 1820 are new records to the Iranian Tabanidae fauna. Diagnostic characters as well as their informative photos are given.